Fundamentals of entrepreneurship (ENT300): Brandy’s bicycle / Ariesha Aki ... [et al.] - Aki, Ariesha; Terry, Jessylyn Jelenny; Bangga, Mary Michelle Ayung (2017)
Brandy’s Bicycle is a new standard and registered bicycle dealership and repair shop that will be operated in Kota Samarahan, Kuching, Sarawak. We have been able to find a shop that is big enough to fit into the design ofthe kind of standard bicycle dealership and repair shop that we intend launching and the shop is located not far from one of the well known university in Kota Samarahan. The name ofthis company comes out from the imagination by the partnership members. It shows that how we positioning our products in customer’s mind so that they can remember our company’s name, simple and easily to pronounce. As for the business, we are providing bicycles with the best quality and affordable prices to our customers. We also sell bicycle parts and accessories from different manufacturers and brands, and also providing bicycle repair and maintenance services. Brandy’s Bicycle is expecting to catch the interest of the university students nearby. Our company plans to build a strong market position in Kota Samarahan area due to the high population of university students in this area. We also set to sell our products to a wide range of customers in and around Kota Samarahan.